BRCA2 Hypomorphic Missense Variants Confer Moderate Risks of Breast Cancer - Shimelis, Hermela; Mesman, Romy L S; Von Nicolai, Catharina; Ehlen, Asa; Guidugli, Lucia; Martin, Charlotte; Calléja, Fabienne M G R; Meeks, Huong; Hallberg, Emily; Hinton, Jamie; Lilyquist, Jenna; Hu, Chunling; et al. (Cancer research, 2017)
Breast cancer risks conferred by many germline missense variants in the BRCA1 and BRCA2 genes, often referred to as variants of uncertain significance (VUS), have not been established. In this study, associations between 19 BRCA1 and 33 BRCA2 missense substitution variants and breast cancer risk were investigated through a breast cancer case-control study using genotyping data from 38 studies of predominantly European ancestry (41,890 cases and 41,607 controls) and nine studies of Asian ancestry (6,269 cases and 6,624 controls). The BRCA2 c.9104A>C, p.Tyr3035Ser (OR = 2.52; P = 0.04), and BRCA1 c.5096G>A, p.Arg1699Gln (OR = 4.29; P = 0.009) variant were associated with moderately increased risks of breast cancer among Europeans, whereas BRCA2 c.7522G>A, p.Gly2508Ser (OR = 2.68; P = 0.004), and c.8187G>T, p.Lys2729Asn (OR = 1.4; P = 0.004) were associated with moderate and low risks of breast cancer among Asians. Functional characterization of the BRCA2 variants using four quantitative assays showed reduced BRCA2 activity for p.Tyr3035Ser compared with wild-type. Overall, our results show how BRCA2 missense variants that influence protein function can confer clinically relevant, moderately increased risks of breast cancer, with potential implications for risk management guidelines in women with these specific variants. Cancer Res; 77(11); 2789-99. ©2017 AACR.
Keywords: studie případů a kontrol; nádory prsu; Humans; Amino Acid Substitution; Mice; Genotype; zvířata; Risk; Breast Neoplasms; riziko; zárodečné mutace; missense mutace; BRCA2 Protein; substituce aminokyselin; myši; ženské pohlaví; Female; Animals; genotyp; lidé; Case-Control Studies; Mutation, Missense; Germ-Line Mutation; Aged; senioři; protein BRCA2